Refleksi Pola Kerukunan Umat Beragama - Arifuddin Ismail (Analisa: Journal of Social Science and Religion, 2010)
In a plural community, harmony among religious followers is undeniable although in fact there have been many social conflicts with religiousnuance in some part of Indonesia. Focus of this research is how the pattern ofharmony in Indonesia connected with social dimension does. Finding of thisresearch shows that religious tolerance will grow up when there is a spacefor dialogue. In social and cultural space discussion among believers will benaturally developed without any coercion. By a local tradition dialog, an egocan decrease indirectly. Even a cloth of religion recognized as identity canbe leaved. Keywords : Dialogue, culture, harmony